Effect of automobile exhaust on blood lead level of lactating Indian cows - Dey, S; Swarup, D; Dwivedi, S K (The Indian Journal of Animal Sciences, 2012)
The effects of automobile exhaust on animal health were assessed by blood lead (Pb) content in adult cows grazed on road side pasture. Median blood Pb level in these cows was estimated as 0.157 ppm and more than 76% of the samples had higher blood Pb concentration than the background levels (0.108 ppm) estimated in samples from rural localities. The results suggest that increased body Pb burden could be a contributing factor for poor health and production which oftenly reported in road side- pasture- grazing cows.